Ligand-based targeting of c-kit using engineered γδ T cells as a strategy for treating acute myeloid leukemia - Branella, Gianna M.; Lee, Jasmine Y.; Okalova, Jennifer; Parwani, Kiran K.; Alexander, Jordan S.; Arthuzo, Raquel F.; Fedanov, Andrew; Yu, Bing; McCarty, David; Brown, Harrison C.; Chandrakasan, Shanmuganathan; Petrich, Brian G.; et al. (Frontiers in Immunology, 2023)
The application of immunotherapies such as chimeric antigen receptor (CAR) T therapy or bi-specific T cell engager (BiTE) therapy to manage myeloid malignancies has proven more challenging than for B-cell malignancies. This is attributed to a shortage of leukemia-specific cell-surface antigens that distinguish healthy from malignant myeloid populations, and the inability to manage myeloid depletion unlike B-cell aplasia. Therefore, the development of targeted therapeutics for myeloid malignancies, such as acute myeloid leukemia (AML), requires new approaches. Herein, we developed a ligandbased CAR and secreted bi-specific T cell engager (sBite) to target c-kit using its cognate ligand, stem cell factor (SCF). c-kit is highly expressed on AML blasts and correlates with resistance to chemotherapy and poor prognosis, making it an ideal candidate for which to develop targeted therapeutics. We utilize γδ T cells as a cytotoxic alternative to ⍺β T cells and a transient transfection system as both a safety precaution and switch to remove alloreactive modified cells that may hinder successful transplant. Additionally, the use of γδ T cells permits its use as an allogeneic, off-the-shelf therapeutic. To this end, we show mSCF CAR-and hSCF sBite-modified γδ T cells are proficient in killing c-kit + AML cell lines and sca-1 + murine bone marrow cells in vitro. In vivo, hSCF sBitemodified γδ T cells moderately extend survival of NSG mice engrafted with disseminated AML, but therapeutic efficacy is limited by lack of γδ T-cell homing to murine bone marrow. Together, these 2 This is a provisional file, not the final typeset article data demonstrate preclinical efficacy and support further investigation of SCF-based γδ T-cell therapeutics for the treatment of myeloid malignancies.